1998
DOI: 10.1111/j.1469-7793.1998.555be.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of activity‐dependent increases of cerebral blood flow by excitatory synaptic activity and spikes in rat cerebellar cortex

Abstract: Mechanisms of activity‐dependent increases in cerebral blood flow (CBF) were examined in rat cerebellar cortex using the laser Doppler flow technique and extracellular recordings of single unit activity and field potentials. Stimulation of the monosynaptic climbing fibre system evoked long‐lasting complex spikes in Purkinje cells, and extracellular field potentials with a characteristic profile that indicated contributions from both passive and active membrane mechanisms. The concomitant CBF increases were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
260
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(290 citation statements)
references
References 34 publications
26
260
4
Order By: Relevance
“…The relationship between neuronal activity and haemodynamic response is still a question under considerable debate (Attwell and Iadecola, 2002;Lauritzen, 2005;Logothetis et al, 2001). However, several studies have shown that increases in local CBF are mainly driven by afferent input to regions of interest (Logothetis et al, 2001;Mathiesen et al, 1998) and are therefore best correlated to local field potentials rather than spiking activity (Masamoto et al, 2008;Mathiesen et al, 1998). It is then plausible that the amperometric signal could be driven by a haemodynamic response subsequent to dopaminergic terminal release and changes in local field activity in the NAc induced by midbrain dopamine neurons.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 99%
“…The relationship between neuronal activity and haemodynamic response is still a question under considerable debate (Attwell and Iadecola, 2002;Lauritzen, 2005;Logothetis et al, 2001). However, several studies have shown that increases in local CBF are mainly driven by afferent input to regions of interest (Logothetis et al, 2001;Mathiesen et al, 1998) and are therefore best correlated to local field potentials rather than spiking activity (Masamoto et al, 2008;Mathiesen et al, 1998). It is then plausible that the amperometric signal could be driven by a haemodynamic response subsequent to dopaminergic terminal release and changes in local field activity in the NAc induced by midbrain dopamine neurons.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 99%
“…This is probably because the majority of the synapses within a column input from other neurons in the cortex, and the hemodynamic response is mostly sensitive to the level of synaptic activity (Mathiesen et al, 1998).…”
Section: N1 and P2 Sep Components Predict The Hemodynamic Response Bementioning
confidence: 99%
“…Recently, a great deal of effort has been devoted to studying the nature of the neurovascular coupling by combining invasive electrophysiological measurements of multiunit activity (MUA) and local field potentials (LFP) with measurements of hemoglobin concentration changes using intrinsic optical imaging and spectroscopy (OIS) (Devor et al, 2003;Sheth et al, 2003) or with measurements of cerebral blood flow (CBF) changes using laser Doppler flowmetry (LDF) (Hoffmeyer et al, 2007;Jones et al, 2001;Mathiesen et al, 1998;Ngai et al, 1999;Thomsen et al, 2004;Ureshi et al, 2004). Despite technical difficulties, progress has been made in combining microelectrode recordings of MUA and LFP, or evoked potentials measured on the scalp, with BOLD fMRI (Logothetis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The current status of these issues has been reviewed recently [62]. In regard to spatial specificity, most notable are the concepts that fMRI imaging signals might be linked more to a large population of neurons displaying alterations in their postsynaptic potentials (as reflected in local field potentials) than to phasic spiking output [63][64][65][66].…”
Section: Functional Imaging Signals Versus Neuronal Activitymentioning
confidence: 99%